Robotic Arm Control through Human Arm Movement Using Accelerometer - Adeeb Ahammed, P.; Prabhu, K Edison (Asian Journal of Electrical Sciences, 2016)
In today’s world there is an increasing need to create artificial arms for different inhuman situations where human interaction is difficult or impossible. Here we propose to build a robotic arm controlled by natural human arm movements whose data is acquired through the use of accelerometers. The development of this arm is based on a accelerometers, which will all be interfaced with the microcontroller. Finally, this prototype of the arm may be expected to overcome the problem such as placing or picking hazardous objects or nonhazardous objects that are far away from the user.